A estrutura da cadeia do avestruz no Brasil: um estudo exploratório. - Bianco, Patricia Perussi (2006)
This study was performed in order to investigate the suplly chain of ostriches and to identify improviment factors for its managment to lead to the consolidation of the criation of ostriches in the brazilian agrobusiness. The work has pratical relevance since the national ostrich breeding has provobed great interest among the business men, livestockers and liberal workers a as new business opportunity for th brazilian agrobusiness. Besides that, the breeders already introduced in the sector are sceking for solutions to the existint problems. The theorical contextualization was approached through two main points: the evaluation of o new supply chain and its management. The research methodology used qas study multi-cases in wich ten breedeing localized in the state of São Paulo were investigated. The conclusion of the accomplished research have showed that the supply chain of ostriches in Brazil is in development so the companies and its partners need to search organization strategies for its viability a new alternative for the brazilian agrobusiness.